Applying Reagents Containing the Thioamide Group in the Flotation of Copper Arsenopyrite Ore - V. I. Ryaboy; E. D. Shepeta; I. V. Ryaboy (International Mineral Processing Congress, 2018)
"The problem of separation of copper minerals and arsenopyrite remains relevant because of environmental requirements. The selective action of reagents with the thioamide group (thioamides) is known in iron sulfide’s flotation of pyrite and pyrrhotite. The aim of this study was to reduce the arsenic content in the copper concentrate when using thioamides by reducing the flotation of arsenopyrite in the flotation of the sulfide part of the skarn scheelite-sulfide ores. We have chosen the most widely used thioamides for the study, such as Z-200. We also synthesized new reagents with the thioamide group. The most selective and the most powerful thioamide copper collector were used for further studies. Reduction of arsenic content in copper concentrates is achieved in the following way: You need to apply a strong thioamide collector with a selective but weak dialkyldithiophosphate collector, or vice-versa, a selective, but a weak thioamide collector should be used with the dialkyldithiophosphate reagent with strong collective properties. The proposed combination presents industrial interest because of its accessibility. The application of thioamides in copper minerals and arsenopyrite selection has showed that these reagents have fewer selective properties than dialkyldithiophosphates. To achieve the comparable recovery of copper using dialkyldithiophosphates requires markedly greater consumption of thioamides, due to their lower hydrophobic ability. The application of a composition of thioamides and dialkyldithiophosphates allows to increase the recovery of copper and to obtain a lower arsenic content in copper concentrates compared to their individual use. The lowest arsenic content in the copper concentrate is obtained in the composition consisting of the newly synthesized thioamide with strong collective properties and selective dialkyldithiophosphate. The addition of even small amounts of xanthate to the composition of thioamides and dialkyldithiophosphates causes a sharp increase in the arsenic content in the copper concentrate without a notable increase in copper recovery."